Service design technology as a tool for the development of the Institute of social services - Sipunova, Nadezhda Valentinova (Социодинамика, 2024)
The purpose of this study is to analyze the features of the service design technology in social services. The object of the research is the institutional features of social services for the population, the subject is the role and essence of service design technology as a tool for the development of the institute of social services. The author provides an analysis of the institutional features of the development of social services, examines the impact of the use of service design technologies in the provision of social services. Special attention is paid to the characteristics of innovative social service practices based on the implementation of service design technology, as well as to the analysis of the development and transformation of institutional functions of social services as a result of the widespread introduction of service design practices in the social sphere. Based on the data of the analysis of best practices of social services, the author also analyzes the processes of formation of new social institutions as a result of the implementation of the service approach in the social sphere, one of which is the institute of regional service commissioners. The main research method is the traditional analysis of documents, generalization of the research of the Institute of Social Services, experience in the implementation of service design technology, as well as analysis of its impact on the processes of transformation of social institutions. The theoretical and methodological basis of the research is the works devoted to the study of the peculiarities of the development of the institute of social services, the introduction of service design technology into the processes of service provision. The main results of this study are conclusions about the special role of service design of social services in ensuring the sustainability of public relations by balancing the implementation of public interests associated with the absence of excessive spending on social services and the interests of small groups meeting their needs at an optimal level through convenient routing and individual design of social services. The author's scientific contribution consists in analyzing the transformation of institutional functions of social services in the implementation of service design technology. The author concludes that the institutional function of social services for reproduction, distribution and exchange also changes with the implementation of the service design approach, becoming simpler and more effective, and the structure of public relations is changing under the influence of the need for new actors and institutional forms of social services with an increased role of interdepartmental interaction.